PENGARUH KOMPETENSI, BUDAYA KERJA, DAN KOMITMEN KERJA TERHADAP PRESTASI KERJA PENDIDIK YANG TERSERTIFIKASI DI LINGKUNGAN SEKOLAH PERMATA HARAPAN PENGARUH KOMPETENSI, BUDAYA KERJA, DAN KOMITMEN KERJA TERHADAP PRESTASI KERJA PENDIDIK YANG TERSERTIFIKASI - Jurnal Ilmiah Manajemen Universitas Putera Batam (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2018)
This research to analysis Competency factor, work culture, and Work commitment the influences towards work achievement of certified educators for certified educators batam city. For kinds of research are Explanatory case study and analysis method that using phat analysis with 135 sample respondent. The method to exam with vapidities person rank and rehabilitees, Alpa cronbach exam toword research instrument. To evaluate in fluencies of Competency factor, work culture and Work commitment towards work achievement of certified educators in Permata Harapan School by using path analysis or standardized regression and calculated trough SPSS program for windows version 22. After had been worked the research and evaluation as method above the result are show that Competency factor work culture and Work commitment has positive influences and significant toward work achievement of certified educators as good as stimulant or partial. Base on data analysis, conclusion that the proposes theoretical model can be used to predict work achievement of certified educators in Permata Harapan School. The variable included in the conceptual model shows a strong pattern of positive relationship so that all the hypothesis proposes in this research study are received well.